2020
DOI: 10.3892/mmr.2020.11600
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of miR‑128‑3p in inhibiting osteoblast differentiation from bone marrow‑derived mesenchymal stromal cells

Abstract: The authors' previous study demonstrated that mir-128 may exert an inhibitory effect on the osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BM-MScs), but its downstream mechanisms remain to be elucidated. The aim of the present study was to investigate the microRNA (miRNA/miR) and mRNA profiles of differentiated and undifferentiated BM-MScs and explore new downstream targets for mir-128. The sequencing datasets of GSe107279 (mirna) and GSe112318 (mrna) were downloaded from the Gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Firstly, we applied hTFtarget ( http://bioinfo.life.hust.edu.cn/hTFtarget#!/ ) to predict putative transcription factors of USP2 in bone marrow tissues. Since the role of ETS1 [ 23 ;] RUNX1 [ 24 ;] CTCF [ 25 ;] E2F4 [ 26 ] and MYC [ 27 , 28 ] in osteogenic differentiation have been reported, we selected them as the research candidates ( Figure 3A ). Subsequently, we knocked down these transcription factors and detected the interference efficiency (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, we applied hTFtarget ( http://bioinfo.life.hust.edu.cn/hTFtarget#!/ ) to predict putative transcription factors of USP2 in bone marrow tissues. Since the role of ETS1 [ 23 ;] RUNX1 [ 24 ;] CTCF [ 25 ;] E2F4 [ 26 ] and MYC [ 27 , 28 ] in osteogenic differentiation have been reported, we selected them as the research candidates ( Figure 3A ). Subsequently, we knocked down these transcription factors and detected the interference efficiency (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…osteoclasts) also contribute to fracture risk. Human iPSCs have successfully been differentiated into osteoclasts (Chen, 2020), but to date this not yet been reported for equine iPSCs and it would be of benefit to measure gene expression profiles in other cell types in the future. Similarly, we did not have access to bone tissue from fracture cases and controls and so were unable to confirm if these differences in expression also occur in vivo at either the gene or protein level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SOSTDC1 has been shown to be involved in bone metabolism, the maintenance of bone density and fracture repair (Tong et al, 2022, Collette et al, 2016). NTRK2 is involved in osteoblast differentiation of MSCs (Zhang et al, 2020) and binding of NTRK2 to its receptor results in the phosphorylation of ERK1/2 which drives the expression of the bone-promoting transcription factors RUNX2 and SP7 (Osterix) (Liu et al, 2018). EPHA3 is a member of the ephrin receptor family and ephrin signalling is involved in bone development and homeostasis (Arthur and Gronthos, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs that participate in the differentiation of osteoblasts have been identified. For example, miR-497-5p (Zhao et al, 2020), microRNA-150-3p (Qiu et al, 2020), miR-708-5p (Wang et al, 2020), and microRNA-497-5p (Liu et al, 2020a) have been shown to promote this process, while miR-30 (Zhang et al, 2020a), miR-129-5p (Yin et al, 2020), miR-128-3p (Zhang et al, 2020b), and miR-17-5p have suppressive effects. In various cell types, miR-425-3p is differentially expressed (Li et al, 2020;Ma et al, 2019), but its function in osteogenesis has not been documented.…”
Section: Discussionmentioning
confidence: 99%